Chewing gum consumption in the United States among children, adolescents and adults. Issue 3 (4th March 2019) - Martyn, Danika M.; Lau, Annette
ABSTRACT: Data regarding chewing gum consumption habits and attitudes were collected for 963 children and adolescents (aged 6–14) and 3150 adolescents and adults (aged 13 years+) in the United States (U.S.) using a dedicated online food frequency questionnaire. A total of 79.6% of children/adolescents reported using chewing gum in the last 3 months, whereas 61.8% of adolescents/adults chewed gum in the previous 6 months. The mean and 90th percentile of consumption among children/adolescents aged 6–14 were 1.95 and 4.71 g day −1, equivalent to 0.75 and 1.78 pieces per day, respectively. Stratification by gender and age brackets revealed that the consumption of chewing gum was more heavily reported in boys compared to girls. Among adolescents/adults aged 13 years and older, the mean and 90th percentile of consumption of chewing gum was estimated to be 2.98 and 7.67 g day −1, or 1.05 and 3.00 pieces per day, respectively. Stratification by gender and by age brackets in this cohort did not reveal any marked patterns although it was noted that there was a decrease in the percent consuming with age (from 87.0 to 34.5%). The most commonly reported chew frequency among all ages was 'two or three times a week' (23.7 to 26.8%). The average and high-level estimates reported herein provide up-to-date estimates of chewing gum consumption in the U.S. Comparisons of the calculated intake values with those reported from the National Health and Nutrition Examination Survey dataset suggests that national nutrition surveys may result in an under-reporting of the percent consumers, but similar estimates for the daily intakes in g day −1 .